Silvopastoral systems benefit invertebrate biodiversity on tropical livestock farms in Caquetá, Colombia - Kinneen, Lois; Escobar, Maria Paula; Hernández, Luis Miguel; Thompson, Jill; Ramos Pastrana, Yardany; Córdoba Suarez, Eric; Romero Sánchez, Miguel Antonio; Barnes, Andrew P.; Quintero, Marcela; Garrat, Michael P. D. (Wiley, 2024)
In the Colombian Amazon, there has been long-term and sustained loss of primary forest threatening biodiversity and climate change mitigation. Silvopastoral practices that integrate trees into livestock production could help address both local economic and wider environmental challenges. We aimed to assess the effects of silvopastoral practices on invertebrate communities on smallholder farms in Caquetá, Colombia. Using sweep nets and malaise trapping, invertebrate communities were compared between traditional pasture, silvopasture and forest edge habitats. Invertebrate communities collected using sweep nets were contrasting among habitat types, communities were significantly different between traditional pasture and forest edge habitats and diversity and evenness were greatest in forest edges compared to traditional pastures. It appears that silvopasture areas, by supporting similar invertebrate assemblages to both traditional pasture and forest edges, may be acting as an intermediate habitat. When individual invertebrate orders were compared, Lepidoptera and Coleoptera were found in greater abundance in the forest edge habitats, while Hemiptera were more abundant in traditional pasture. Hemipterans are often pests of forage plants in pasture systems and these differences in abundance may have implications for ecosystem services and disservices. Silvopastoral approaches cannot replace the unique biodiversity supported by native forests but could deliver benefits for invertebrate conservation and ecosystem services if integrated into landscapes.